2008
DOI: 10.1037/0033-295x.115.2.426
|View full text |Cite
|
Sign up to set email alerts
|

The dimensionality of the remember-know task: A state-trace analysis.

Abstract: This article addresses the issue of whether the remember-know (RK) task is best explained by a single-process or a dual-process model. All single-process models propose that remember and know responses reflect different levels of a single strength-of-evidence dimension. Thus, across conditions in which response criteria are held constant, these models predict that the RK task is unidimensional. Many dual-process models propose that remember and know responses reflect two qualitatively distinct processes underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(199 citation statements)
references
References 105 publications
(189 reference statements)
5
194
0
Order By: Relevance
“…In such studies, amnesic patients have sometimes (18,19), but not always (20,21), exhibited a higher frequency of Know judgments than controls (as if they experience the butcher-onthe-bus phenomenon more often than controls). However, in recent years, much evidence has accumulated showing that, despite receiving standard instructions, participants usually make Know judgments for Old decisions that are associated with lowto-medium confidence, not high confidence (22)(23)(24). Thus, Know judgments reflect relatively weak memory (as well as weak source recollection), not strong memory in the absence of source recollection.…”
Section: Discussionmentioning
confidence: 99%
“…In such studies, amnesic patients have sometimes (18,19), but not always (20,21), exhibited a higher frequency of Know judgments than controls (as if they experience the butcher-onthe-bus phenomenon more often than controls). However, in recent years, much evidence has accumulated showing that, despite receiving standard instructions, participants usually make Know judgments for Old decisions that are associated with lowto-medium confidence, not high confidence (22)(23)(24). Thus, Know judgments reflect relatively weak memory (as well as weak source recollection), not strong memory in the absence of source recollection.…”
Section: Discussionmentioning
confidence: 99%
“…In this paradigm, partici-pants are instructed to give a "know" response if the test item only seems familiar, while they must give a "remember" response if they consciously recall having seen the test item before. It is unclear to what extent this subjective experience actually dissociates between two qualitatively different processes, or even if the two responses arise from different processes at all (W. Donaldson, 1996;Hirshman & Master, 1997;Dunn, 2004Dunn, , 2008.…”
Section: Chapter 4 Secondary Processes In Recognitionmentioning
confidence: 99%
“…Unitization refers to the creation of a novel entity that is "more than the sum of its parts", just as a word is more than a collection of letters or a painting more than a collection of brushstrokes, a topic often studied in Gestalt psychology (Wagemans et al, 2012a,b) as well as in the study of the perception of both simple and complex stimuli (Townsend & Wenger, 2015). The formation of unitized representations may be encouraged by semantic elaboration of either word pairs (Graf & Schacter, 1985;Prior & Bentin, 2003, 2008 or image pairs (Kan et al, 2011), resulting in the storage of stronger associative information. As in the present study, repetition of intact word pairs has been found to enhance memory for their association beyond any benefit from repeating the component items (Kilb & Naveh-Benjamin, 2011;Parks & Yonelinas, 2015), suggesting that associative information is a unitized representation of the complete pair that can be strengthened separately from representations of items.…”
Section: What Is Associative Information?mentioning
confidence: 99%
“…That these processes retrieve different kinds of information implies that item and associative information are stored separately and may be represented in qualitatively different forms accessible only to particular processes. However, arguments in favor of this view have relied on measures of recognition accuracy that are not diagnostic of the types of processes involved (Dunn, 2004(Dunn, , 2008Wixted, 2007;Pratte & Rouder, 2012) and that are only reliable under the strong assumption of item and associative independence (Curran & Hintzman, 1995;Hillstrom & Logan, 1997;Ratcliff et al, 1995). In contrast, item and associative memory are often correlated: Item recognition is affected by the presence of an intact association, even when it is irrelevant to the task (Tulving & Thompson, 1973;Clark & Shiffrin, 1987) and while participants are able to separately assess memory for items and associations, they are influenced by the strength of both items and associations when doing so (Buchler et al, 2008;Aue et al, 2017).…”
Section: Introductionmentioning
confidence: 99%